THE ROLE AND IMPACT TO THE EDUCATION QUALITY OF ICT - Zakirova, D.Yu. (Educational Research in Universal Sciences, 2023)
This article purpose is highlights importance of the using information-communication technologies in the education and its impact to the education quality.